The double life cycle of Lepidapion argentatum, a promising candidate for the biological control of French Broom. Issue 8 (3rd August 2019) - Kerdellant, E.; Thomann, Th.; Vitou, J.; Giusto, C.; Simonot, O.; Sheppard, A.; Sforza, R. F. H.
ABSTRACT: Lepidapion argentatum (Gerstaecker) (Brentidae) is a weevil from the Mediterranean region collected and recorded from French broom ( Genista monspessulana ) (L.) LAS Johnson (Fabaceae), a major invasive plant in the USA. We studied feeding and oviposition of L. argentatum under laboratory conditions. Overwintering adults can oviposit in either seed-pods or stem tips of French broom. Larvae in seed-pods consume seeds whereas those in stems develop inside a gall. The development time of L. argentatum in stem galls ranged from 34 to 40 days at mean 23.67 ± 2.43°C. The double ability of L. argentatum to develop in stems and pods appears not to have been recorded in Coleoptera and rare in other phytophagous insects. Our finding increases its potential value as a biocontrol agent against French broom.